A guide to hydropower plant development by the private sector in Iran - Nikraz, Magid; Ghaeli, M.; Ghaeli, M.; Taghvaei, S.; Nikraz, Hamid (International Centre of Hydropower, 2010)
Hydropower plant development is, undeniably, a very complex undertaking, often lasting several years and requiring a large initial capital investment. As a consequence, such projects frequently run into difficulties raising the necessary capital. For this reason, investment in hydropower plants is a major issue for governments and power providers. There are numerous countries worldwide that have a significant albeit underutilized capacity for hydropower development. Iran is an example of such a country. It is a suitable candidate for the further development of hydropower mainly due to its favorable topological layout. That is, it is one of the world's most mountainous countries and also contains a number of major rivers and streams originating in the mountains. Due to inadequate investment schemes, however, the country is currently operating far below its actual hydropower potential. Focusing attention, therefore, on the method of funding such projects and the development of adequate economic models in the hydropower context is absolutely imperative.In this study, the process of investment for small hydropower plants with a maximum capacity of 10 MW is investigated. This investment process takes into considering all factors prior to construction including: the purchasing of electricity by the Ministry of Energy, water rationing, and water distribution schemes during the various seasons. To aid in this process, a methodology to guide the investment process is proposed. This guide will allow prospective investors in small hydropower plants to ascertain: where is the best location in the country to invest their capital amongst a number of alternatives; when to expect a return on their initial capital investment; and statistics relating to the performance of the hydropower plant both in terms of power / revenue generation. The results will also have ramifications for investors worldwide.